The Dominant Influence of Marketing in the 21st Century The Marketing Leviathan - Kitchen, P.; Kitchen, P. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Marketing has become the dominant connecting mode of expression between business and non-business organisations and customers and consumers. However, there are some misgivings about marketing in the 21st century. This volume addresses the positive and negative elements of marketing and questions 'Is marketing a leviathan in today's societies?'.